Designing Math Trails-based Hypothetical Learning Trajectory to Promote Students’ Numeracy Skill - Nazzun Sholikha Nurin; Iwan Junaedi; Adi Nur Cahyono (Universitas Negeri Semarang, 2023)
This study aims to design a Math Trails-based Hypothetical Learning Trajectory (HLT) to promote students’ numeracy skill. This research uses design research consisting of three stages: (1) preliminary design, (2) teaching experiments, and (3) retrospective analysis. This research is focused on the preliminary design stage. The HLT component consists of learning objectives that are adjusted to numeracy indicators, learning activities using task designs on MathCityMap, and hypothetical learning process that refers to the steps of mathematical modeling process to solve numeracy problems. The results of this study are HLT in the form of 8 task designs that have been designed, reviewed by experts, and revised according to suggestions and received a score of 4,6 out of 5 from experts. For further research, experimental research can be carried out to examine the increase in numeracy skills through this designed HLT.